Influence of Semen Collection Frequency and Seasonal Variations on Fresh and Frozen Semen Quality in Thai Native Roosters - Maruay Pimprasert; Theerapat Kheawkanha; Wuttigrai Boonkum; Vibuntita Chankitisakul (Animals, 2023)
This study aimed to determine the effects of the frequency of semen collection (once, twice, and thrice weekly) and seasonal variations on the fresh and frozen semen quality of Thai native roosters throughout the year. Data on temperature and humidity were collected and used to calculate the temperature–humidity index (THI). The average temperature and THI were lower in the winter than in the rainy season and the summer (p < 0.05). In contrast, the average relative humidity was not different among the seasons but was higher in the rainy season (p > 0.05). None of the fresh or frozen semen quality parameters were influenced by the frequency of semen collection, but the season did have an effect. The highest sperm concentration was obtained in the winter (p < 0.05). In contrast, the lowest sperm concentration was found during the rainy season, which presented the highest humidity. Regarding the frozen semen quality, the highest malondialdehyde concentration and the lowest motility were found in the summer (p < 0.05). In conclusion, semen collection can be conducted thrice per week for a consecutive year without affecting semen quality while maximizing sperm production. However, the highest sperm production was obtained in the winter, which is also a suitable season for producing semen for cryopreservation.